Crisis Communication : Theory and Practice. - Zaremba, Alan Jay (Taylor and Francis, 2014)
Crises happen, and when they do organizations must be prepared to communicate effectively with their internal and external stakeholders, and with the public. Today, crisis communication has evolved from a public relations paradigm of reactive image control to an examination of both internal and external communication, which requires proactive as well as reactive planning. This innovative text adds theoretical coverage and practical application to the more traditional study of crisis communication through case analysis. It prepares students by:.--providing a theoretical framework for understand.